Impacts of liberalizing rice milling sector in Malaysia using system dynamics framework - Chung, Bonhee (2015)
The Malaysian government has regulated the rice industry through price controls, provision of various subsidies and monopoly on rice importation among other policies. The government’s main objectives are to achieve rice self-sufficiency, improve paddy farmers’ income and keep rice affordable for low income households in particular. By means of price fixation, the government imposes the guaranteed minimum price at farm level and ceiling price at retail level. As a consequence, the government has effectively restricted the profitability of rice millers who play an important role by purchasing rough paddy from farmers and then producing white rice for consumers. The government has also directly intervened in the rice milling sector by establishing public mills and provided them a rice miller subsidy as well as an electricity subsidy for producing affordable rice,known as ST15 in local market. For many years, there have been concerns over market liberalization in many countries around the world. The Malaysian government is expected to comply with the WTO’s demand for market liberalization, which translates into removals of the protectionist policies. Some important questions arise over how the liberalized market would cope with structural changes and more importantly whether it can stabilize rice prices in Malaysia. The change in market structure are most likely to have sequential effects on key variables such as rice prices, production, consumption, import, rice millers’ capacity utilization and capital investments, milling efficiency represented by the head rice recovery ratio and the rice self-sufficiency level. Using a system dynamics approach to modeling the rice industry in Malaysia, the author developed a system dynamics model in an attempt to illustrate the behavioral patterns of the rice milling sector in the context of whole rice industry in Malaysia. And then the author ran simulations of policy change such as removals of price controls and the subsidies, and examined their impacts on the key variables. The author also ran simulations of policy alternatives that can stabilize rice prices and again examined their impacts on the other key variables. The simulation results of policy changes show that the removal of price controls has considerable impacts on the key variables, while the removal of rice miller and electricity subsidies has little impacts on the key variables. The simulation results of policy alternatives suggest that terminating the monopoly on rice importation is the most effective way to stabilize rice prices, even though Malaysia’s rice self-sufficiency stays at the minimum level. Malaysia is able to stabilize rice prices and achieve the 100% selfsufficiency goal through land conversion from non-granary areas to granary areas; however, there are financial, physical and technical constraints to initiate the land development. Malaysia can also stabilize rice prices and achieve the goal by permitting paddy importation into Malaysia at the expense of local paddy farmers.